2015
DOI: 10.3390/v7010352
|View full text |Cite|
|
Sign up to set email alerts
|

Epimedium koreanum Nakai Displays Broad Spectrum of Antiviral Activity in Vitro and in Vivo by Inducing Cellular Antiviral State

Abstract: Epimedium koreanum Nakai has been extensively used in traditional Korean and Chinese medicine to treat a variety of diseases. Despite the plant’s known immune modulatory potential and chemical make-up, scientific information on its antiviral properties and mode of action have not been completely investigated. In this study, the broad antiviral spectrum and mode of action of an aqueous extract from Epimedium koreanum Nakai was evaluated in vitro, and moreover, the protective effect against divergent influenza A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 63 publications
0
30
0
Order By: Relevance
“…Dried EF was purchased from Yeongcheon Oriental Herbal Market (Yeongcheon, South Korea) and stored in the KM-Application Center herbarium (registration number, #354) Korea Institute of Oriental Medicine(KIOM), after verification of identity by Prof. Ki Hwan Bae (Chungnam National University, Daejeon, Korea). The WEF was filtered through standard sieves (150 μm, Retsch, Haan, Germany), concentrated by lyophilization, and stored at −20°C until use (Cho et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dried EF was purchased from Yeongcheon Oriental Herbal Market (Yeongcheon, South Korea) and stored in the KM-Application Center herbarium (registration number, #354) Korea Institute of Oriental Medicine(KIOM), after verification of identity by Prof. Ki Hwan Bae (Chungnam National University, Daejeon, Korea). The WEF was filtered through standard sieves (150 μm, Retsch, Haan, Germany), concentrated by lyophilization, and stored at −20°C until use (Cho et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Madin-Darby Canine Kidney (MDCK, ATCC CCL-34, NBL-2), African green monkey kidney (Vero, ATCC CCL-81), and RAW264.7 (murine macrophage, ATCC TIB-71) cells were cultured in Dulbecco's Modified Eagle's Medium (DMEM; Lonza, Walkersville, MD) containing 10% fetal bovine serum (FBS; Cellgro, Manassas, VA, USA) and 1% antibiotics (100 U/ml penicillin and 100 μg/ml streptomycin) at 37°C with 5% CO 2 as described previously (Cho et al, 2015 ). Influenza A/PuertoRico/8/34 H1N1, green fluorescent protein (GFP)-tagged Influenza A/PuertoRico/8/34 H1N1 (PR8-GFP), and NDV-GFP were propagated in the allantoic fluid of 10-day-old chicken embryos.…”
Section: Methodsmentioning
confidence: 99%
“…Quercetin also demonstrated a dose-dependent antiviral activity against poliovirus type 1, HSV-1, HSV-2, and respiratory syncytial virus (RSV) in cell cultures [60,83]. Epimedium koreanum Nakai, which contains quercetin as the major active component, has been shown to induce secretion of type I IFN, reducing the replication of HSV, Newcastle disease virus (NDV), vesicular stomatitis virus (VSV) in vitro, as well as influenza A subtypes (H1N1, H5N2, H7N3 and H9N2) in vivo [18]. Hung et al [51] have suggested possible mechanisms whereby quercetin may exert its anti-HSV activity.…”
Section: Antiviral Activity Of Flavonolsmentioning
confidence: 99%
“…Interestingly, one of the many biological effects of flavonoids is their antiviral activity. For example, apigenin extracted from Ocimum basilicum showed a potent antiviral activity against adenoviruses and hepatitis B virus (Chiang et al, 2005), whereas quercetin demonstrated a dose-dependent antiviral activity against herpes simplex virus (Lyu et al, 2005), Japanese encephalitis virus (Johari et al, 2012), hepatitis C virus in vitro (Rojas et al, 2016); and influenza A subtypes in vivo (Cho et al, 2015). Similarly, genistein was shown to inhibit HIV infection in resting CD4 T cells through interference with HIV-mediated actin dynamics (Guo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%